Aplikasi Komunikasi Data Menggunakan Instant Messengger Dan SMS Gateway di PT. Sarandi Karya Nugraha Sukabumi - Ridwan (LP2M CBI Press, 2017)
Existence of information which quickly and accurate is true very expected by each and everyone which is communicating, not the problem of if us each other dealing with what becoming the source of information. Other but again its problem if the communications blocked with difference of distance or place which not enable us to be able to give or accept information directly and will be more be complicated if beside difference of place, also that information should be able to be kept as reference or requirement of this othera. The trouble happened PT. Sarandi Karya Nugraha where each every division or department even with departmental office of branch in this case department Marketing departement need the existence of communications to confirm or advise about existing problems each every its department or ask departmental information of other.Then is intention of this writing is to give application and knowledge about a communications system, conducive of inter department relation or division can intertwin better. As for this writing method for example using field study, where information and also data obtained from result of interview with side of menejer departmental head and or existing division and also passstudy of kepustakaan. Trouble this require to get attention, in order not to happened wrong effect misunderstanding or is late of accepted information him. Thereby pursuant to analysis which have been done in PT. Sarandi Karya Nugraha this, its its is existence of internal issue of communication and with existence of network facility which have been woke up will be more add its benefit made of communications system as communications medium. Information quickly will add work productivity and also minimized the happening of misunderstanding, that thing can reach with existence of communications system. This system can be done by exploiting network system, developing application software for the communications of, saving order into database and also evaluate data order if needed. Keywords : Information, knowledge, application, communication, networking